Automated Exploration, Capture and Photogrammetric Reconstruction of Interiors Using An Autonomous Unmanned Aircraft - Lieret, Markus; Kogan, Vladyslav; Hofmann, Christian; Franke, Jörg (2021 IEEE International Conference on Mechatronics and Automation, ICMA 2021, 2021)
Digital environment models are gaining importance in various fields of application. High-resolution digital models of the current environment structure can facilitate planning manufacturing plants or allow monitoring construction processes precisely. While systems for the fully automated capturing of terrain structures are already in use in outdoor areas, the digitisation process in indoor areas is usually carried out manually. Since global navigation satellite systems are not available in complex indoor areas, other solutions for robust and precise autonomous localization and navigation have to be used and validated. Furthermore, it is more intricate to ensure that all required areas and structures are taken into account with sufficient accuracy during the capture process. Within this paper, we present a fully automated system for data acquisition and digitisation of complex indoor environments. Using an autonomous unmanned aircraft equipped with a suitable sensor system, intelligent algorithms for navigation, exploration and photogrammetric reconstruction, a previously unknown environment is autonomously explored and a three-dimensional model is reconstructed. Extending the related research, we demonstrate that also within indoor environments unmanned aircraft are applicable for the autonomous acquisition of images for photogrammetric reconstruction. Within the evaluation, we validate the functionality of the overall system and the accuracy of the resulting point clouds of the environment.
CRIS-Team Scopus Importer:2021-10-01
Keywords: autonomous unmanned aircraft; environment perception; photogrammetry; robot navigation

Automated in-house transportation of small load carriers with autonomous unmanned aerial vehicles - Lieret, Markus; Kogan, Vladyslav; Döll, Sebastian; Franke, Jörg (2019 IEEE 15th International Conference on Automation Science and Engineering (CASE), 2019)
Within the last years, the application of unmanned aerial vehicles (UAV) in the delivery and logistics sector has become focus of various research projects. This can be traced back to the fact that UAVs allow a flexible and fast transportation and extend the flow of materials by the third dimension. While the feasibility of outdoor transports with UAVs has already been shown in the scope of pilot projects the indoor transportation of cargo with UAVs lags behind. This can be ascribed to both legal restrictions and missing technical innovations. To advance the technical implementation we developed a scalable hard and a software system for the flexible and automated in-house transportation of small load carriers with autonomous UAVs. In addition, a tracking system that is both suitable for the basic tracking of a UAV during the flight and for the precise tracking required to pick up and set down the cargo is presented. The presented system is based on a newly developed cargo drone including a lightweight and energy-efficient load handling device. Its features and setup will be highlighted before the resulting integral system is evaluated within a paradigmatic use case whereby a prepared cargo is autonomously picked up, transported and delivered to a predefined destinatio